Underhood Thermal Simulation - John Willio, Joracin Geraldini (My University, 2020)
With an increasing necessity to control emissions and providing a sustainable transport system, it is essential to predict the cooling system performance early in the development process of the coach bus. Setting up a simulation methodology that accurately predicts the cooling system performance requires integrating cooling system performance predictions with the whole underhood thermal simulation model. The integrated simulation model is incorporated with a scope to find hot air recirculation and engine compartment backpressure, which plays a pivotal role in estimating the cooling system's performance in the coach bus. In this work, dual-stream heat exchanger model is implemented for all three heat exchangers, namely CAC, Oil cooler, Radiator cooler. Each heat exchangers have a hot and cold interface that is provided with porous media coefficient values. The cold and hot fluid flow surpasses the respective interfaces with the specified resistance values, and thereby, heat transfer occurs. Q maps from the supplier data are used to calculate the heat exchangers' local heat transfer rate. The commercial code used to build this simulation model is STAR-CCM+. The simulation model is tested with four different running conditions and compared with the physical test values. The pressure drop values have an excellent agreement with the supplier data from which the usage of porous coefficients is justified. The heat exchangers' power should not be a problem as they are specified through the 'Q map.' The Oil coolers, one of the heat exchangers, do not have test data, which causes deviations in CAC and radiator parameters. The lack of test data for oil coolers and radiation not being modeled causes the recirculation temperature predicted by the model to vary from test results.
Keywords: STAR-CCM+; CFD; Heat transfer; dual stream heat exchangers; GT-SUITE